2010
DOI: 10.1111/j.1523-5378.2009.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Helicobacter pylori Infection, Co‐Morbid Infections, Gastrointestinal Symptoms, and Circulating Cytokines in African Children

Abstract: There is a high prevalence of asymptomatic H. pylori infection in recently resettled African refugee children. Gastrointestinal symptoms were not predictive of H. pylori nor of helminth infections. Serum cytokines, particularly IL-5, IL-10, and TNFalpha, were significantly elevated in children with malaria and helminth infections but not in those with H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 58 publications
3
16
1
4
Order By: Relevance
“…[10] showed significant differences in H. pylori prevalence between Pacific Island (49.0%) vs. Maori (26.7%) and Asian (24.7%) vs. European adolescents (13.7%). Several studies on children and adolescents in Asia showed prevalence rates ranging from 20% to 84% [12–15]. Overall, as expected, the H. pylori prevalence rates from the Asia‐Pacific region were high except among the white population of Australia and New Zealand.…”
Section: Prevalencesupporting
confidence: 57%
See 2 more Smart Citations
“…[10] showed significant differences in H. pylori prevalence between Pacific Island (49.0%) vs. Maori (26.7%) and Asian (24.7%) vs. European adolescents (13.7%). Several studies on children and adolescents in Asia showed prevalence rates ranging from 20% to 84% [12–15]. Overall, as expected, the H. pylori prevalence rates from the Asia‐Pacific region were high except among the white population of Australia and New Zealand.…”
Section: Prevalencesupporting
confidence: 57%
“…We have grouped the studies according to the different geographical regions for ease of reference (Table 1). There were 10 studies from the Asia‐Pacific region on adults [2–11] and 4 on children [12–15]. Li et al.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…T. trichiura is a candidate for future study because it was prevalent in Tumaco children [18], and Al and T. trichiura infections in poor Brazilian children were associated with enhanced IL-5 and IL-10 production by peripheral blood mononuclear cells along with hyporesponsiveness to mitogen stimulation in culture [51]. Our data are also consistent with elevated serum levels of IL-5, IL-10, and TNFa with an elevated IL-10 ⁄ IL-12 ratio in asymptomatic African refugee children concurrently infected with Hp, malaria, and helminths [52].…”
Section: Parasites and H Pylori In Colombianssupporting
confidence: 81%
“…There are continued reports of the lack of relationship between H. pylori infection and abdominal symptoms [10,17–19]. In Nigeria, Senbanjo et al.…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%